The harder they come [large type] - Boyle, T. Coraghessan (Harperluxe, 2015)
Set in contemporary Northern California, The Harder They Come explores the volatile connections between three damaged people -- an aging ex-Marine and Vietnam veteran, his psychologically unstable son, and the son's paranoid, much older lover -- as they careen towards an explosive confrontation.